PUBLISHING ARTICLES ON TEACHING ISSUES: NAVIGATING CHALLENGES AND IMPLEMENTING EFFECTIVE STRATEGIES - Roza Bahodirova; Lobar Baxodirova; Baratova Madina; Ergasheva Saboxat (TADQIQOTLAR, 2026)
Abstract This article examines the growing importance of publishing research on teaching issues in modern education. In today’s rapidly developing educational environment, teachers are expected not only to teach but also to contribute to academic knowledge through research and publication. The paper discusses the major challenges educators face while preparing scholarly articles, including lack of methodological knowledge, difficulties in academic writing, limited time, and problems related to data analysis. Furthermore, the article highlights practical strategies that can help teachers improve the quality of their manuscripts and successfully publish in national and international journals. The study also emphasizes the role of institutions in supporting teacher research and professional development. Academic publishing is presented as a powerful tool for innovation, reflective teaching, and the improvement of educational systems worldwide.